2022
DOI: 10.1007/s11998-022-00630-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an image-based measurement instrument for gloss characterization

Abstract: Gloss is one of the main attributes to describe the appearance of surfaces and objects, as it contributes to the general quality perception. Gloss is a multidimensional quantity of which ‘specular gloss’ is the most commonly applied attribute. Specular gloss meters are standardized and widely used in industry. However, their readings correlate only partially to the general visual gloss impression, which also comprises distinctness-of-the-reflected-image (DOI), haze, contrast and surface-uniformity attributes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Color measurements using the photo-based image analysis approach employed by did not consider tooth luster, nor was luster measured in that study. Thus, the Gurich group may have registered inaccurately lower color readings than the actual in vivo tooth color in the non-peroxide group, because identical colors with higher levels of luster register as a darker shade than those with a lower luster level [25][26][27][28], and this effect is further magnified by the typically higher levels of backscattered light or luster in photographs recorded at 900 such as those used by the industry-recommended angles of 200, 400or 600 [26]. Because the current study demonstrated that tooth luster increased significantly in the teeth treated with the nonperoxide formulations, butit decreased significantly in the teeth treated with the peroxide strips, it seems reasonable to assume that this unmeasured, but essential variable gave rise to misleading conclusions about whitening efficacy in the Gurich study.…”
Section: Discussionmentioning
confidence: 99%
“…Color measurements using the photo-based image analysis approach employed by did not consider tooth luster, nor was luster measured in that study. Thus, the Gurich group may have registered inaccurately lower color readings than the actual in vivo tooth color in the non-peroxide group, because identical colors with higher levels of luster register as a darker shade than those with a lower luster level [25][26][27][28], and this effect is further magnified by the typically higher levels of backscattered light or luster in photographs recorded at 900 such as those used by the industry-recommended angles of 200, 400or 600 [26]. Because the current study demonstrated that tooth luster increased significantly in the teeth treated with the nonperoxide formulations, butit decreased significantly in the teeth treated with the peroxide strips, it seems reasonable to assume that this unmeasured, but essential variable gave rise to misleading conclusions about whitening efficacy in the Gurich study.…”
Section: Discussionmentioning
confidence: 99%
“…It is based on the earlier design from Ref. [6], extended with a 0° camera (item 10) and several light sources at 45° and 10° angles of incidence (items 11 and 12). This extended iGM device complies to the widely known standards for a parallel beam 60° specular gloss meter ( [3], [4]).…”
Section: Image-based Gloss Metermentioning
confidence: 99%
“…At the same time it captures more advanced measurements relevant to many industrial applications. It is an extension of a previously designed image-based gloss meter (iGM, such as presented in [5] and [6]), which processes the captured reflected light source image to evaluate new metrics for the attributes DOI, haze and contrast. [6] Sample measurements illustrated the versatility and utility of the system for several materials, including anisotropic surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychophysical models aim to predict how humans perceive gloss based on visual cues, such as highlights, shading, and contrast. They consider factors like observer angle and lighting conditions to estimate gloss perception [10][11][12][13][14][15][16][17][18]. Ferwerda et al proposed a psychophysically-based model of surface gloss perception, which uses image synthesis techniques to describe and control the appearance of glossy surfaces in synthetic images [11].…”
Section: Introductionmentioning
confidence: 99%